1994
DOI: 10.1111/j.1745-7599.1994.tb00933.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Problems in the Elderly

Abstract: Sleep problems in older adults are so common that nearly half of all hypnotic prescriptions written are for persons over 65 years old. Although normal aging affects sleep, the practitioner should evaluate the many factors that cause insomnia: medical illness, psychiatric illness, dementia, alcohol and/or polypharmacy, restless legs syndrome, periodic leg movements, and sleep apnea syndrome. Nonpharmacologic treatment of sleep disorders is preferred. The nurse practitioner can assess and manage elderly patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…No single measurement tool which adequately met the measurement requirements of the study was identified from the literature. A Sleep Pattern Assessment Tool (SPAT) was therefore formulated as a composite instrument, the development of which was in part informed by the literature ( Morgan, 1987; Morin & Gramling, 1989; Prinz et al ., 1990 ; Johnston, 1994; Foley et al ., 1995 ; Riedel et al ., 1995 ). The SPAT was devised to monitor each participant's sleep pattern over a period of seven days, with baseline data being collected on the first two days prior to the intervention part of the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…No single measurement tool which adequately met the measurement requirements of the study was identified from the literature. A Sleep Pattern Assessment Tool (SPAT) was therefore formulated as a composite instrument, the development of which was in part informed by the literature ( Morgan, 1987; Morin & Gramling, 1989; Prinz et al ., 1990 ; Johnston, 1994; Foley et al ., 1995 ; Riedel et al ., 1995 ). The SPAT was devised to monitor each participant's sleep pattern over a period of seven days, with baseline data being collected on the first two days prior to the intervention part of the study.…”
Section: Methodsmentioning
confidence: 99%
“…Insomnia or disturbed sleep is a common complaint of older people and has been shown, in an American study, to affect 50% of individuals residing in the community and 70% of those in long‐term care ( Johnston, 1994). Monane (1992) suggests that this is related to both subjective and objective changes in quality and quantity of sleep, and that it may be of short‐term or long‐term nature.…”
Section: Introductionmentioning
confidence: 99%
“…Common sleep problems in the elderly include insomnia and excessive daytime sleepiness. Insomnia affects about 50% of those living in the community and about 70% of those in nursing homes (Johnston, 1994). In community residing elderly, the prevalence of daytime sleepiness is about 20% (Whitney et al, 1998), but the prevalence in nursing homes is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have focused on the effect of sleep problems on SE. Sleep complaints are common among the elderly, including those living in nursing homes . Excessive daytime sleepiness is one of the most frequent sleep complaints among the geriatric population, and it affects approximately 10%–30% of older adults .…”
Section: Introductionmentioning
confidence: 99%
“…Sleep complaints are common among the elderly, including those living in nursing homes. 16,17 Excessive daytime sleepiness is one of the most frequent sleep complaints among the geriatric population, and it affects approximately 10%-30% of older adults. 18,19 A recent report examined the relationship between sleep problems and activities in residents of long-term care facilities, and the report suggested that those with sleep problems exhibit lower levels of SE and activity.…”
Section: Introductionmentioning
confidence: 99%